Morphology analysis of unlabeled red blood cells based on quantitative differential phase contrast microscopy. Issue 8 (13th March 2022) - He, Linna; Shao, Meng; Yang, Xiao; Si, Li; Jiang, Mengduo; Wang, Tao; Ke, Zeyu; Peng, Tao; Fang, Shu; Zhang, Shengzhao; Ouyang, Xilin; Zhao, Gang; et al.
Abstract: The current classical blood smear technique to observe the morphology of single red blood cells (RBCs) for classification is a laborious and error‐prone process. To objectively evaluate the morphology of blood cells, we established a method of computational imaging based on a programmable light emitting diode array. By using quantitative differential phase contrast (qDPC), we characterized the morphology of unlabeled RBCs as well as blood smears. By focusing on comparing the difference of imaging between unlabeled RBCs and stained RBCs under multimode microscopic imaging technology, we demonstrated that qDPC could clearly differentiate discocytes and spherocytes in both unlabeled RBCs and blood smears. The phase map provided by quantitative phase imaging further enhanced the classification accuracy. According to statistical analysis from morphological indexes, the qDPC imaging has a significantly improvement in non‐circularity, texture inhomogeneity and equivalent diameters of cells. Thus, this method has a significant superiority in the capability to analyze the morphology of RBCs and could be applied to clinical assays for determining morphological, functional, and structural deterioration of RBCs.